Cultural Differences in Critical Thinking Style: A Comparison of U. S. and Chinese Undergraduate Agricultural Students - Peng Lu; Scott Burris; Matt Baker; Courtney Meyers; Glenn Cummins (Journal of International Agricultural and Extension Education, 2021)
This study aimed to compare critical thinking styles between students studying agriculture in the U.S. and China. A survey of critical thinking styles was administered to two groups of students in U.S. (n = 104) and China (n = 103). Multivariate analysis of variance (MANOVA) was applied to determine if there were significant differences in critical thinking styles between the two groups. Results indicate that U.S. students tended to prefer an engaging critical thinking style, whereas Chinese students tended to prefer an information seeking critical thinking style. These differences between critical thinking style preferences may be explained by students’ cultural backgrounds. This study can help agricultural educators understand the differences in critical thinking style preferences among culturally-diverse students. Further, it provides empirical evidence to guide agricultural educators seeking to adopt effective pedagogical approaches to cultivate critical thinking among students from diverse cultural backgrounds. This study provides fresh insight into the individualism and collectivism theory by explaining the cross-cultural differences in critical thinking style between U.S. and Chinese agricultural students.
Keywords: Cultural Differences in Critical Thinking Style